Pengaruh Pendidikan Agama Islam dalam Keluarga dan Budaya Religius Sekolah terhadap Ketaatan Beragama Peserta Didik - Nur Hapipa Siregar; Zulhammi Zulhammi; Suparni Suparni (ISLAMIKA, 2023)
This study aims to determine and test empirical data related to the influence of Islamic religious education in the family and school religious culture on the religious obedience of students in private madrasah aliyah in the Barumun sub-district, Padang Lawas district. This research uses associative method. The associative method is research that aims to determine the relationship, influence between two or more variables with a correlational and regression approach to quantitative data obtained from research objects, namely students from Private Madrasah Aliyah in Barumun sub-district, Padang Lawas district. The sample of this research is 105 people. The type of analysis used in this research is multiple linear and correlation test which is described descriptively. The results of this study are, first, there is a significant influence between Islamic religious education in the family on the religious observance of private madrasah aliyah students in the Barumun sub-district, Padang Lawas Regency, with a coefficient of determination (R2) of 0.214 which means that Islamic religious education in the family affects religious observance students by 21.4%). Second, the results of the study show that there is a significant influence between the religious culture of the school on religious observance, with a coefficient of determination (R2) of 0.145, which means that the religious culture of the school influences the religious observance of students at Private Madrasah Aliyah in Barumun District by 14.5%. Third, the results of the study show that there is a significant influence between Islamic religious education and school religious culture on religious observance together, with a coefficient of determination (R2) of 0.190, which means that Islamic religious education and school religious culture affect the religious observance of madrasah students private aliyah in the Barumun district of 19.0%.